Long-term effects of left-behind experience on adult depression: Social trust as mediating factor - Wang, Yan; Yang, Shuai; Wang, Feng; Liu, Zhijun (Frontiers in Public Health, 2022)
Background: Despite much attention paid to the mental health of left-behind children, there has not been sufficient research on whether and how left-behind experiences have long-term effects on adults among the general population. This paper aims to evaluate the long-term effects of left-behind experience on adult psychological depression. Methods: By using the China Labor-force Dynamics Survey in 2018 (CLDS 2018), we assessed depression by the Center for Epidemiological Studies, Depression Scale (CES-D) and used a cut-off score of 20 for detecting depression (Yes=1, No=0). The Binomial logistic regression was used to compare the odds ratio across groups. We used the KHB-method in the mediation analysis, to measure the indirect effect of social trust on the relationship between left-behind experience and depression. Results: The rate of depression (χ2= 17.94, p< 0.001) for the children who have left-behind experience (LBE) (10.87%) was higher than the children who have non-left-behind experience (N-LBE) (6.37%). The rate of social trust (χ2= 27.51, p< 0.001) of LBE (65.70%) was lower than N-LBE (75.05%). Compared with the other three groups, left-behind experience occurred in preschool (OR=2.07, p < 0.001, 95% CI= [1.45, 2.97]) was more likely to suffer from depression. The indirect effect of social trust (OR=1.06, p<0.01, 95% CI= [1.02, 1.10]) is significantly on the relationship between LBE and psychological depression, with the total effect (OR=1.71, p<0.001, 95% CI= [1.27, 2.31]) and direct effect (OR=1.62, p<0.01, 95% CI= [1.20, 2.18]) are both significantly. The proportion of indirect effect in the total effect is 10.69%. Conclusion: The left-behind experience that occurred in childhood has a significantly negative effect on adult psychological depression, in which preschool left-behind experience played the most critical role. Social trust is the mediating factor associated with left-behind experience and psychological depression. To mitigate the long-term effects of the left-behind experience on psychological depression, parents need to be prudent about the decision-making of migration in the preschool stage of their children. and subsequent policies should strengthen social work targeting vulnerable youth groups especially those with left-behind experience at an early age in terms of their psychological depression.